Realizing the Right to Sanitation in Deprived Urban Communities: Meeting the Challenges of Collective Action, Coproduction, Affordability, and Housing Tenure. (April 2015) - McGranahan, Gordon
Summary: There are serious institutional challenges associated with low-cost sanitation in deprived urban communities. These include a collective action challenge, a coproduction challenge, a challenge of affordability versus acceptability, and a challenge related to housing tenure. This paper examines these challenges, revealing both the importance of community-driven sanitation improvement and its difficulties. The nature of the challenges, and the means by which two successful community-driven initiatives have overcome them, suggest that while recognizing the human right to sanitation is important this should not be taken to imply that typical rights-based approaches are the appropriate means of realizing this right.